(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the intricate task of translating English idiomatic expressions into other languages, shedding light on the challenges faced by translators in conveying the nuanced meanings embedded in these culturally specific phrases. Idiomatic expressions, deeply rooted in the cultural and linguistic fabric of a language, present formidable obstacles in achieving accurate equivalence during translation. The paper examines the divergent structures and idiomatic variations across languages, emphasizing how these disparities pose difficulties in finding precise equivalents. Through illustrative examples, the article delves into the complexities of preserving the idiomatic richness while ensuring comprehension in the target language. Additionally, it explores the impact of cultural context on idiomatic interpretation and how translators navigate these cultural intricacies. By addressing the multifaceted nature of translating idioms, this article contributes to a deeper understanding of the challenges inherent in bridging linguistic and cultural gaps in the realm of translation.